Barreiras atitudinais no serviço público na ufersa: uma análise à luz da teoria do reconhecimento - Oliveira, Camila Jéssica Neres de (Universidade Federal Rural do Semi-Árido, 2018)
This work aims to investigate the existence of attitudinal barriers in the work environment of the Federal Rural University of the Semi-Arid. By attitudinal barriers, the concept brought by the Brazilian Law of Inclusion of the Person with Disability (Law nº 13.146 / 15) was used, they are attitudes that prevent or impair the participation of the handicapped in equal conditions and opportunities with the other people. The law introduced this concept, since the elimination of architectural barriers did not prove sufficient for the full inclusion of the disabled in the various social spaces, since the attitudinal barriers were impeding the full social interaction. Still, with a sociological scope, the research was based on Axel Honneth's Theory of Recognition. It dealt more specifically with the third sphere of theory, despite a broad explanation to understand the whole theory. It is based mainly on the sphere of solidarity that research demonstrates the importance of a work environment free of attitudinal barriers so that the physically handicapped can reach their maximum productive capacity as well as their self-realization. The method used was qualitative, the technique was semi-structured interviews, which allowed not only to have established questions, but also to ask other questions during the interview with the purpose of elucidating the facts. The main conclusion was that there are attitudinal barriers in the work environment of the Universidade Federal Rural do Semi-Árido, which hinder the performance of activities by the disabled and negatively compromise their self - realization
Keywords: Barreiras atitudinais; servidores deficientes; Teoria do Reconhecimento; autorrealização; Attitudinal barriers; poor servers; Theory of Recognition; selfrealization; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES